2023
DOI: 10.2196/44188
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators of and Barriers to Accessing Hospital Medical Specialty Telemedicine Consultations During the COVID-19 Pandemic: Systematic Review

Abstract: Background The COVID-19 pandemic accelerated the digital transition in health care, which required a rapid adaptation for stakeholders. Telemedicine has emerged as an ideal tool to ensure continuity of care by allowing remote access to specialized medical services. However, its rapid implementation has exacerbated disparities in health care access, especially for the most susceptible populations. Objective We aimed to characterize the determinant factor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 117 publications
0
7
0
1
Order By: Relevance
“…Se detectaron factores relacionados con aspectos tecnológicos (conectividad, dispositivos o analfabetismo digital), aspectos estructurales (lugar, energía eléctrica, convivientes o interrupciones), institucionales (protocolos, recomendaciones, normativas o convenios con prestadores), clínicos (motivos de consulta inapropiados a la modalidad o restricciones en el examen físico) y vinculares (contacto más distante con pacientes conocidos solo por teleconsulta, trabajo solitario con menor intercambio con colegas, etc.). En forma consistente, Habib et al (45) reportaron que la mayor barrera percibida (68,7%) fueron las dificultades técnicas; mientras que Cunha et al (46) identificaron las siguientes: falta de acceso a servicios de Internet; falta de acceso a dispositivos tecnológicos; disparidades raciales, étnicas y etarias; baja alfabetización digital; falta de recursos económicos; barreras del idioma; falta de cobertura por parte del seguro médico; preocupaciones sobre la privacidad y confidencialidad de los datos; disparidades geográficas; y la necesidad de pruebas diagnósticas complementarias o la entrega de resultados de las pruebas. En nuestro estudio, la edad y la cobertura de seguro médico también fueron variables que estuvieron presentes de manera reiterada en los relatos.…”
Section: Discussionunclassified
“…Se detectaron factores relacionados con aspectos tecnológicos (conectividad, dispositivos o analfabetismo digital), aspectos estructurales (lugar, energía eléctrica, convivientes o interrupciones), institucionales (protocolos, recomendaciones, normativas o convenios con prestadores), clínicos (motivos de consulta inapropiados a la modalidad o restricciones en el examen físico) y vinculares (contacto más distante con pacientes conocidos solo por teleconsulta, trabajo solitario con menor intercambio con colegas, etc.). En forma consistente, Habib et al (45) reportaron que la mayor barrera percibida (68,7%) fueron las dificultades técnicas; mientras que Cunha et al (46) identificaron las siguientes: falta de acceso a servicios de Internet; falta de acceso a dispositivos tecnológicos; disparidades raciales, étnicas y etarias; baja alfabetización digital; falta de recursos económicos; barreras del idioma; falta de cobertura por parte del seguro médico; preocupaciones sobre la privacidad y confidencialidad de los datos; disparidades geográficas; y la necesidad de pruebas diagnósticas complementarias o la entrega de resultados de las pruebas. En nuestro estudio, la edad y la cobertura de seguro médico también fueron variables que estuvieron presentes de manera reiterada en los relatos.…”
Section: Discussionunclassified
“…The personal limitations at hand can limit telemedicine's effectiveness, as the disabled will have a decreased ease of use for this technology (Yi et al, 2021). The utilization of telemedicine has seen increased use in our research period, especially following the COVID-19 pandemic, which can be attributed to global lockdown events and preventative procedures (Cunha et al, 2023), (Feldman & Baum, 2021. Promising results in the field of chronic disease management, as well as optimistic conclusions for alleviating worker shortages, demonstrate further positive outcomes of utilizing telemedicine (Nguyen et al, 2023), (Parish & Chan, 2021).…”
Section: General Research Perspectivementioning
confidence: 99%
“…Across the 14 included studies that were identified to contain trends from the Ethical research perspective, many trends exhibited results contrary to the previous research perspectives, in that there continue to be existing concerns regarding telemedicine, its barriers to implementation, and additional training for medical professionals. An abundance of concerns regarding telemedicine remain within the various fields of applications alongside healthcare professionals (Cunha et al, 2023). Access to technology and the internet have remained the most prominent barriers to telemedicine use (Cunha et al, 2023).…”
Section: Ethical Research Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the remote medical care model is more effective in addressing the medical requirements of older adults postoperative patients. Based on a systematic review, an individual's social, cultural, and digital technological competence is a crucial factor in determining the benefits derived from telemedical care (14). Consequently, this study diligently endeavored to impart suitable training to patients and their families enrolled in the telemedicine system.…”
Section: The Telemedicine System Can Better Meet the Medical Requirem...mentioning
confidence: 99%